PERILAKU SUAMI TERHADAP ALAT KONTRASEPSI PRIA (VASEKTOMI) DI DESA UJUNG PULO CUT KECAMATAN BAKONGAN TIMUR KABUPATEN ACEH SELATAN TAHUN 2013 - dedi irawan; Alam Bakti; Eddy Syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
Abstract Family planning is efforts to take apart or to plan the number of child and pregnancy using contraception. The family planning aims to increase the prosperity of mother and child in addition to realize a norm of happy and prosperous small family as a base for realization of prosperous society by control the birth and growth of the population. This Reseach is a study using qualitative method in order to get a depth information about the behavior of husband to the male contraception (vasectomy) at Desa Ujung Pulo Cut subdistrict of Bakongan Timur Regency of South Aceh in 2013. The primary data is collected through indepth interview to the informan while the secondary data is collected by document study about village and sub district. Informan in this reseach are 7 persons. i.e. the population of Desa Ujung Pulo Cut with the background of education, age, number of child and different work. All of informan are Moeslim and etnic of Aceh. The results of study indicates that the informan did not know what is the Male Operation Method (MOP). 5 of 7 informans said that did not know this method. This is caused by the lack of knowledge and understanding of informan for the lack of socialization of MOP program. The guidance and training and socialization of Family Planning program specially Male Operation Method (MOP) must be implemented continuously by PPLKB, Community Health Centre to enable husband understand this method.